Peripartum pubic symphysis separation – Current strategies in diagnosis and therapy and presentation of two cases. Issue 6 (June 2015) - Herren, C.; Sobottke, R.; Dadgar, A.; Ringe, M.J.; Graf, M.; Keller, K.; Eysel, P.; Mallmann, P.; Siewe, J.
Abstract Background During spontaneous vaginal delivery, pubic symphyseal widening is normal. Common changes are reversible after complication-free birth. However, cases of peripartum symphysis separation are rare. There is no consensus in the literature on how to treat pregnancy-related pubic symphysis separation. Methods This review used a literature-based search (PubMed, 1900–2013) and analysis of 2 own case reports. Studies with conclusions regarding management were particularly considered. Results Characteristic symptoms, suprapubic pain and tenderness radiating to the posterior pelvic girdle or lower back, may be noted 48 h after delivery. Pain on movement, especially walking or climbing stairs, is often present. Conservative treatments, such as a pelvic brace with physiotherapy and local interventions such as infiltration, are successful in most cases. Symptom reduction within 6 weeks is the most common outcome, but can take up to 6 months in some cases. Surgical intervention is needed in cases of persistent separation. Anterior plate fixation is offered as a well-known and safe procedure. Minimally invasive SI joint screw fixation is required in cases of combined posterior pelvic girdle lesions. Summary Postpartum symphyseal rupture can be indicated with the rare occurrence of pelvic pain post-delivery, with sciatica or lumbago and decreased mobility. The diagnosis is made on clinical findings, as well as radiographs of the pelvic girdle. Conservative treatment with a pelvic brace is the gold standard in pre- and postpartum cases of symphysis dysfunction.